PLANTER PABRIK GULA PEKALONGAN MENGGUGAT UPAH MASA CULTUURSTELSEL - Wening - Pamudiasih (Universitas Negeri Yogyakarta, 2014)
Abstract Two main things leading to the selection of Java to be the area of investment by Dutch colonial were the presence of the labors and the cheap land or in another words it was the lower production cost. The prerequisites of the condition establishment were put in the period of Cultuurstelsel i.e. when the political and economic obstacles determined their form in the coordinating institution of the natives’ power use as mediation for the deployment. For the natives, the presence of the financial capital began to be sensed when the plantation industry was established. The industrial work pattern emerged, which was a combination of agricultural employment of export plants with manufacturing employment. The concrete form was sugar factories. The issues mainly arose in how the manner of the Gubernemen conditioned various social strata, from the elite top to small farmers to get involved to support the planting projects in ondernemings and the process of turning the sugarcanes into sugar.